Experimental studies of parameters of combine harvester during sunflower harvesting (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article presents the results of experimental studies of the agroengineering technology of combine harvester sunflower. The dependences of the influence of the technological parameters of the grain harvester on the change in engine loading, fuel consumption, seed loss and threshing quality, which are economically expedient to use during sunflower harvesting, are revealed. Effective parameters and indicators of the grain harvester are offered. In field experimental studies of the impact on the threshing quality and fuel efficiency, the rational limits of the rotation speed of the threshing drum, the speed of the fan, and the technological gap in the under-drumming of the grain harvester were determined. The authors established that the basic indicators of the agro-engineering technology of combine harvesting of sunflowers are harvester losses of 72 kg/ha at an engine load of 43% and fuel consumption of 12 l/ha. Indicators that can be normalized: losses - 82 kg/ha with engine load of 67% and fuel consumption of 15.3 l/ha. The authors established that the loss indicators were at least 24 kg/ha with an engine load of 63% and a fuel consumption of 14.5 l/ha. Experimental studies have established that the threshing drum rotation speed of 450-460 rpm, the fan rotation speed of 1000 rpm, and the gap between the drums of 27 mm are necessary for the operation of the grain harvester when harvesting sunflowers. The authors established that the efficiency at basic indicators is 878 euros/ha, and at indicators where losses were minimal 809 euros/ha. Therefore, it is advisable to thresh with losses, in our case 82.3 kg/ha, but with higher quality threshing because, in the further sale of sunflower, there will be no price reduction.
Keywords: combine; sunflower; grain consumption; clogging; agroengineering